2017
DOI: 10.1161/jaha.116.005344
|View full text |Cite
|
Sign up to set email alerts
|

Role of Circulating Fibroblast Growth Factor 21 Measurement in Primary Prevention of Coronary Heart Disease Among Chinese Patients With Type 2 Diabetes Mellitus

Abstract: BackgroundFibroblast growth factor 21 (FGF21) has demonstrated beneficial effects on lipid and carbohydrate metabolism. In cross‐sectional studies, an association of raised circulating FGF21 levels with coronary heart disease (CHD) was found in some but not all studies. Here we investigated prospectively whether baseline serum FGF21 levels could predict incident CHD in subjects with type 2 diabetes mellitus and no known cardiovascular diseases.Methods and ResultsBaseline serum FGF21 levels were measured in 352… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 38 publications
1
28
0
Order By: Relevance
“…Serum FGF21 levels were significantly increased in patients with insulin resistance and T2DM [ 21 ]. One recent study found that FGF21 level was an independent predictor of the raised incidence of CHD and may confer higher risks of CHD in T2DM subjects [ 22 ]. Elevated level of circulating FGF21 was correlated with the incidence of hypertension in community-dwelling adults [ 23 ] and dyslipidemia in CHD patients [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serum FGF21 levels were significantly increased in patients with insulin resistance and T2DM [ 21 ]. One recent study found that FGF21 level was an independent predictor of the raised incidence of CHD and may confer higher risks of CHD in T2DM subjects [ 22 ]. Elevated level of circulating FGF21 was correlated with the incidence of hypertension in community-dwelling adults [ 23 ] and dyslipidemia in CHD patients [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the same cohort of subjects, higher serum FGF21 levels predicted development of major adverse cardiovascular events in 169 patients with CAD at baseline [30]. In another study of 3528 T2D patients, the optimal cut-off value of serum FGF21 levels at baseline was 206 pg/mL, levels above which predicted incident CHD over a median follow-up of 3.8 years [31]. In our previous study of 9697 T2D patients not on statin at baseline, higher plasma FGF21 levels predicted CVD events over 5 years follow-up [9].…”
Section: Discussionmentioning
confidence: 91%
“…Circulating FGF21 levels are recently viewed as an indicator of the development and progression of some chronic diseases 11,[33][34][35][36][37][38][39] . Furthermore, a negative relationship was found between circulating FGF21 levels and aerobic fitness in men 15,16) .…”
Section: Discussionmentioning
confidence: 99%